2012
DOI: 10.1111/j.1365-2915.2012.01037.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of tick‐borne pathogens in ticks from migratory birds in the Baltic region of Russia

Abstract: We report the finding of tick-borne encephalitis (TBE)-virus in indigenous Ixodes ricinus (L.), 'Candidatus Neoehrlichia mikurensis' in exotic Ixodes frontalis (Panzer) and Rickettsia aeshlimannii in exotic Hyalomma marginatum Koch subadult ticks detached from 18.5% (107/577) infested migratory birds in the Baltic region of Russia. This is the first record of human pathogenic 'Candidatus N. mikurensis' in I. frontalis ticks. Moreover, seven other pathogens were identified in I. ricinus ticks. Spotted Fever Gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 30 publications
3
29
0
1
Order By: Relevance
“…It has been reported that TBEV positive ticks were detached from birds in Estonia, Western Siberia region of Russia, Baltic region of Russia and Sweden Mikryukova et al, 2014;Movila et al, 2013;Waldenström et al, 2007). Our previous data show that Borrelia burgdorferi, Anaplasma phagocytophilum, Rickettsia helvetica and Babesia spp.…”
Section: Discussionmentioning
confidence: 90%
“…It has been reported that TBEV positive ticks were detached from birds in Estonia, Western Siberia region of Russia, Baltic region of Russia and Sweden Mikryukova et al, 2014;Movila et al, 2013;Waldenström et al, 2007). Our previous data show that Borrelia burgdorferi, Anaplasma phagocytophilum, Rickettsia helvetica and Babesia spp.…”
Section: Discussionmentioning
confidence: 90%
“…africae could be an example of a tick-borne disease imported to another region by livestock trade, like the occurrence of SFG rickettsioses associated with this Rickettsia in the West Indies, after cattle parasitized with A. variegatum were imported from Senegal in the early 1800s (Kelly 2006). Another possible route is the carriage of infected ticks by migrating birds, because they act as transport carriers of many species of the Ixodidae family and therefore as long-distance vectors for several pathogens including Rickettsiae spp., like R. aeschlimannii (Movila et al 2012). It should be noted that Israel is located on the main route of bird migration from Africa to Europe and Asia, thus this route of introduction seems possible (Harrus et al 2011).…”
Section: Discussionmentioning
confidence: 96%
“…Seven species of ticks have been reported to be infected by C. Neoehrlichia mikurensis: I. ricinus [48]; I. persulcatus [5,15]; I. ovatus [1]; Ixodes frontalis [57]; Ixodes hexagonus [30]; Dermacentor reticulatus [29,30]; and Haemaphysalis concinna [13]. It should be emphasized that the infection rates of C. Neoehrlichia mikurensis are highest among the Ixodes species, indicating that these are the primary vectors; the importance of the other tick genera as vectors is disputable, as they rarely carry C. Neoehrlichia mikurensis ( Table 1).…”
Section: Vectors Reservoirs and Transmissionmentioning
confidence: 99%